La fragmentation actancielle : vers une analyse « interfacielle » des infinitives de perception directe - Marsac, Fabrice (Wydawnictwo Naukowe UAM, 2012)
This study proposes an alternative analysis of syntactic infinitives of direct perception: the current approach, spanning various fields of linguistics, attempts to articulate the morphosyntactic characteristics of these structures with their different logical, semantic, cognitive, lexical and grammatical properties. The perspective adopted for this purpose is based on a well known computer process: (de) fragmentation.
An Alternative Analysis of Syntactic Infinitives of Direct Perception Conducted with the Aid of the Concept of Fragmentation
Keywords: infinitive constructions governed by a verb of perception; the concept of fragmentation; syntax-semantics interface; linguistics and computer science